Highlights of European Heart Rhythm Association Scientific Documents - Parry, Nicola (MD Conference Express, 2014)
This article disuccses medical conditions and devices addressed in the most recent European Heart Rhythm Association (EHRA) scientific documents, which typically deal with novel areas that lack a sufficient evidence base to support firm guidelines. The aim of these documents is to provide sound advice from experts, based on the available scientific data, for emerging areas in the management of arrhythmias in Europe.